Evaluation of surface finish technology in the manufacture of Oxide-Oxide ceramic matrix composites. Issue 4 (15th February 2021) - Tontisakis, A.; Simpson, W.; Lincoln, J.; Dhawan, R.; Opliger, M.
Abstract: Oxide-Oxide ceramic matrix composites (Ox-Ox CMCs) enable improved performance properties relative to titanium, inconel and other high-temperature alloys, as high-temperature components in the aerospace and advanced energy sectors due to their low density, oxidation and corrosion resistance, and high heat resistance. However, the high surface porosity and roughness of Ox-Ox CMCs can be problematic in some applications, especially where airflow, drag and friction play a factor in overall performance. The present study explores the application of an Ox-Ox CMC surfacing film designed to co-cure and sinter with composite parts manufactured using Ox-Ox pre-impregnated fabrics with the intention of providing improved surface finish. This surfacing film aims to reduce surface roughness, improve smoothness and airflow, reduce surface porosity and improve resistance to thermal cycling by minimizing microcracking. The film is based on Ox-Ox chemistry compatible with current systems in the market and can withstand temperatures up to 1400 °C. Surface properties and mechanical properties are evaluated and reported on Ox-Ox CMC laminates prepared with and without surfacing film. Results indicate that the Ox-Ox CMC surfacing film provides meaningful improvement in surface quality and in damage tolerance. Marginal reduction in fiber volume percentage was observed due to the increased matrix contribution from the surfacing film.